Pengawasan Pemerintah Terhadap Izin Pelaksanaan Pengelolaan Hasil Sedmimentasi Laut - Wael, Yanti; Nendissa, Renny Heronia; Holle, Erick Stenly (PATTIMURA Law Study Review, 2024)
The increasing activities of marine sedimentation results can damage the utilization of natural resources in coastal areas and small islands in the waters, for that effective supervision from the government is needed so as not to cause conflict so that its implementation can be fully felt by coastal communities. However, there are problems in the management of marine sedimentation results both in terms of regulation and government authority, so it is interesting to examine whether the regulations on marine sedimentation management permits and their management authority have met the provisions of laws and regulations. The purpose of this study is to determine and explain the form of government supervision of marine sedimentation management and the legal consequences of the government not supervising the management of marine sedimentation results. The research method used in this writing is the normative juridical research method with a legislative approach and a conceptual approach. The results of this study can be concluded that government supervision of marine sedimentation management permits cannot run effectively because there are some unclear formulations of norms, and derivative regulations are needed regarding the authority of related Ministry Institutions, such as the Ministry of Marine Affairs and Fisheries and the Ministry of Energy and Mineral Resources which have the potential to overlap authority so as to hinder supervision, and the legal consequences of the government not supervising the management of marine sedimentation results are due to the conflicting legal norms, namely Government Regulation Number 26/2023 which is contrary to Law Number 32/2014 and the like. So that the implementation of Government Regulation Number 26/2023 is null and void.